Wound healing activity of Dillenia ochreata leaves ethanol extract in Wistar rats - Muharni Muharni; Annisa Amriani; Fitrya Fitrya; Anazir Mukafi (GarVal Editorial Ltda., 2022)
Context: Dillenia ochreata is a medicinal plant used traditionally for scabies treatment. D. ochreata leaves contain secondary metabolites of triterpenoids, phenolics, and steroids that have the potential to accelerate the wound healing process. Aims: To determine the effect of the ethanolic extract of D. ochreata leaves on the speed of healing of burns and incisions. Methods: The test animals were divided into six groups: a positive control group (1% silver sulfadiazine ointment for burns and 10% povidone-iodine ointment for wound incision), a negative control group, and four treatment groups with an ointment concentration of 2.5, 5, 7.5, and 10%. Burns were made using a heated iron plate, and incision wounds were made using a sterile scalpel blade with a length of 3 cm. Parameters observed included burn area, incision length, percent recovery, and histopathology. Results: It was observed that the 10% concentration of D. ochreata leaf ethanol extract showed the best results in healing burns and incision wounds, with 100% healing within 12 days for burns and five days for incisions. The treatment group had a significantly different wound healing activity (p<0.05) compared with the negative control and was not significantly different (p>0.05) from the positive control. Conclusions: D. ochreata leaf ethanol extract (10%) could accelerate the healing of burns and incisions.